BLUE FIRE SEBAGAI SUMBER IDE PERANCANGAN IDENTITAS VISUAL DAN PROMOSI IJEN BATIK DI BONDOWOSO MELALUI DESAIN KOMUNIKASI VISUAL - Sriwahyuni, Titin; Herry Prilosadoso, Basnendar (CITRAWIRA : Journal of Advertising and Visual Communication, 2020)
Ijen Batik is one of the new batik industries in Tamanan Subdistrict, Bondowoso Regency, which has its own characteristics compared to other batik industries, namely from the main motive inspired by the blue fire Ijen Crater, as one of the best known natural attractions in Bondowoso. The motif coloring uses the spray technique which produces a gradation color which is a distinctive feature for Ijen Batik. In its development, promotion is carried out only from mouth to mouth and there is no visual identity and promotional media used by Ijen Batik, many people inside and outside Bondowoso do not know about this batik industry, so it is necessary to design a visual identity in accordance with the character of the company and promotional media through communication design. visuals in order to produce an effective media to introduce and promote to the wider community. The initial stage of this design is by collecting data through the approach of observation, interviews, analyzing data with qualitative methods, SWOT analysis and promotional design methods, so that Ijen Batik can create a visual identity according to the company's character, namely using blue fire as a design concept that differentiates it from other industries. The identity created is then applied to various promotional media such as stationery, sign systems, packaging, paper bags and merchandise, posters, billboards, banners, and websites that visually look thematic to form a distinctive image. It is hoped that this design can make this industry known to the public with its uniqueness and character and can have a positive impact on the development of Ijen Batik.